REPETISI DALAM KARANGAN MAHASISWA DAN PENANGANANNYA - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
It is certainly true that repetition plays very important role in sentence and discourse writing because its existence is intended to give stress on linguistic expressions emphasized in the sentence or discourse in which it occurs. However, in composition writing, it is also often found repetitions which do not show any clear function as emphatic devices, and their occurrence tends to bore the readers. These types of repetition reflect the lack of the writers’ ability in producing more interesting and variative sentences. To avoid such phenomena, the knowledge of discourse cohesiveness should always be exposed in any composition writing class because this theory describes various ways of creating cohesiveness besides the repetition itself.